The Contribution of Modern Linguistic Studies to the Development of Arabic Teaching Methods: إسهامات الدراسات اللغوية الحديثة في تطوير طرائق تعليم اللغة العربية - Muhammad Irvan; Nanang Qosim; Abd Faishol (Institut Muslim Cendekia, 2025)
This study aims to analyze the conceptual and procedural contributions of modern linguistics in transforming Arabic language teaching methods. While studies on modern linguistics are abundant, a research gap exists where previous research remains predominantly theoretical-descriptive, lacking applicable guidance for classroom practitioners. The novelty of this research lies in the systematic integration of the four pillars of modern linguistics (phonology, morphology, syntax, and semantics) with the development of material selection strategies based on